ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA PEGAWAI NEGERI SIPIL PADA BADAN PERTANAHAN NASIONAL KABUPATEN BOYOLALI - Desy Herma Fauza; Yohan Wismantoro (MEDIA, 2014)
The purpose of this research is to exam the influences of leadership, organizational commitment, and job environment in the organization toward job’s satisfaction and also increasing of the employee’s performance. The responder of this research were 80 employee’s of Agrarian Office of Boyolali Regency. SPSS for Windows v.18 program is being used to analyzed the collected data. The analysis are proven that leadership, organizational commitment, and job environment in the organization will bring a positive impact and increasing the job’s satisfaction significantly. Furthermore, job’s satisfaction and organizational commitment will bring a positive effect and increasing of employee’s performance significantly. Leadership and  job environment, however, are not significantly related to the employee’s performance, influenced by the intervening variable is employee job’s satisfaction. From seven hypotheses that proposed, only five hypotheses supported, there are the  first, second, third, fourth, and sixth hypotheses.This empirical results indicated in order to increase the job’s satisfaction in Agrarian Office of Boyolali Regency, needs to put an attention in the leadhership, organizational commitment,  job environment, and other factors. It is expected increasing of  employee  job’s satisfaction then projected employee’s performance is also likely to increase., so it can minimize the delay of a certificate endorsement which is still a lot of outstanding requests that can not be resolved in accordance with the incoming request.